Weed control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Control of weeds is an essential aspect of crop production. Weeds compete with crops for water, nutrients and sunlight; if they are not properly controlled crop yields will suffer. In the most extreme case, severe weed infestation can lead to a total crop